Investigation of the resilience of Hungarian counties with regard to the coronavirus epidemic - Greutter-Gregus, Éva; Koncz, Gábor; Némediné Kollár, Kitti (Studia Mundi – Economica, 2023)
Epidemics have been a part of human life for centuries. The topicality of the manuscript is given by the fact that the coronavirus epidemic that broke out in 2019-2020 resulted in the emergence of a global crisis, and its negative effects can still be felt today. COVID has affected spatial structural factors and the everyday functioning of both urban and rural settlements, creating a shocking crisis situation, rewriting people’s daily lives and the functioning of the economy. In our opinion, adaptivity and the ability to react to external influences are very important in the life of long-term sustainable settlements in the 21st century, which can be described by the concept of resilience (Pirisi 2019, Szalai - Fabula, 2022)The measures taken to tackle the epidemic resulted in social isolation and a deterioration in people’s quality of life and economic situation. The aim of this study is to examine the resilience of the Hungarian counties in the light of the pandemic period.